THE EFFECT OF REPEATED READING STRATEGY IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT AT THE EIGHT GRADE STUDENTSOF SMPN 36 PEKANBARU - Destina Kasriyati; Maharani Maharani (ELT-Lectura, 2018)
Based on the result of observation that students got some difficulties to understand the content of reading comprehension, particularly main ideas, detail information, vocabulary, identify information, word reference and generic structure. The purpose of this research was to find whether the students who received in class experiment of repeated reading strategy had different skill in reading comprehension than students who did not receive treatment of the strategy at the second grade of SMPN 36 Pekanbaru. The design of this research was Experimental Research. This research was conducted on Jan 2018. The population of this research was the second grade of SMPN 36 Pekanbaru. The sample of this research were 2 classes as control and experiment class. Based on the test result, it was found that the average score of post-test was 85.33 and pre test was 71. It means that the result of post test was getting higher than pretest. In conclusion, the use of repeated reading strategy could increase students reading comprehension in narrative text. There was different ability between experment and control class.